2011
DOI: 10.1080/15564886.2011.629774
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Behaviors in Corrections: Informal Social Control and Institutional Responses in a State Prison System

Abstract: Self-injurious behavior among inmates remains a significant problem facing correctional institutions despite a lack of research on the topic. This study employs a content analysis of 352 incidents of self-injurious behavior documented by the South Carolina Department of Corrections over a 30 month period. The results from our analysis indicate that self-injury disproportionately occurs when social controls are absent. Self-injury was primarily associated with stressors both inside and outside of prison, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Such high prevalence rates result in substantial mental health needs and pose a number of challenges to the criminal justice system. For instance, mental health symptoms in prison have been linked to violence, self-harm, suicide, victimization [ 4 7 ], and to a reduced willingness or capacity of prisoners to participate in daily activities and prison programs, which in turn may limit their well-being and rehabilitation [ 8 , 9 ]. Moreover, high levels of mental health symptoms may result in a higher use of prison healthcare services, and subsequently increase institutional costs.…”
Section: Introductionmentioning
confidence: 99%
“…Such high prevalence rates result in substantial mental health needs and pose a number of challenges to the criminal justice system. For instance, mental health symptoms in prison have been linked to violence, self-harm, suicide, victimization [ 4 7 ], and to a reduced willingness or capacity of prisoners to participate in daily activities and prison programs, which in turn may limit their well-being and rehabilitation [ 8 , 9 ]. Moreover, high levels of mental health symptoms may result in a higher use of prison healthcare services, and subsequently increase institutional costs.…”
Section: Introductionmentioning
confidence: 99%
“…Administrators should also consider 'use of force' protocols when responding to inmates who self-injure as these inmates may be less compliant when compared to inmates who do not self-injure (Doty, Smith, & Rojek, 2012). For example, Young, Justice and Erdberg (2006) revealed that inmates who self-injure themselves are over eight times more likely to harm treatment staff when compared to inmates who did not engage in self-injurious behaviors.…”
Section: Self-injurious Behaviors Occurring In Corrections (Sib)mentioning
confidence: 99%
“…Like other forms of mental health vulnerability, inmates who self-injure while incarcerated can be categorized by several key factors. Compared to inmates with no institutional record of self-injury, these inmates are more likely to be on institutional restriction for a medical or physical condition, have disciplinary infractions, and require major mental health treatment (Doty, Smith, & Rojek, 2012;Smith & Kaminski, 2010;Wichmann, Serin, & Abracen, 2002). One study examined a sample of 40 male prison inmates who engaged in repeated self-injurious behavior and who had been diagnosed with anti-social personality disorder (Virkkunen, 1976).…”
Section: Self-injurious Behaviors Occurring In Corrections (Sib)mentioning
confidence: 99%
“…The quality of health care in correctional settings varies within facilities and commonly correctional institutions rely on health care in the community for treatment of serious health concerns (Gates et al, 2014). Despite recommendations to provide health care post-suicide attempt, correctional policies often specify punitive responses, such as placing incarcerated adults in segregated housing, after a suicide attempt (DeHart et al, 2009;Doty et al, 2012;Konrad et al, 2007). Punitive responses in practice can be detrimental as a study of completed suicides in California prisons found that over 60 percent of suicides were preventable if correctional staff had responded to prior suicidal behaviors with treatment rather than punitive responses (e.g., placement in segregated housing; Patterson & Hughes, 2008).…”
Section: Introductionmentioning
confidence: 99%